METHOD TO IMPROVE BANDWIDTH OF MICROSTRIP ANTENNA - MRS. NAMRATA F. ANSARI; PROF. DR. RAMAPATI MISHRA (International Journal of Innovations in Engineering Research and Technology, 2021)
For high speed internet, multimedia communication and broadband services more broader bandwidth is required. Microstrip Antenna is famous for its small structure , but inherently microstrip antennas are narrow band antennas.The areas of application open to microstrip antennas have been limited by their low operating bandwidth .Various techniques are used to enhance the bandwidth of microstrip antenna. This paper discusses bandwidth enhancement techniques employed on microstrip patch antennasusing multi-layer configurations with vertically stacked resonator geometries.IE3D software is used for the design of Microstrip Antenna.